Auditing nursing care related to weaning neonates from mechanical ventilation in neonatal intensive care units - Mina Salimi; Anahita Masoumpoor; Azam Shirinabadi Farahani; Nezhat Shakeri; Fatemeh Alaee Karharoudy; Hossein Shiri (Tehran University of Medical Sciences, 2016)
Background & Aim: Mechanical ventilation is one of the most common treatments in neonatal intensive care unit and is however associated with many complications. One of the ways to reduce complications is providing nursing care according to standards. This study was conducted with the aim of determining the conformity of nursing care related to weaning neonates from mechanical ventilation to the standards in neonatal intensive care units. Methods & Materials: In this descriptive study (the audit), 105 nursing cares related to weaning neonates from mechanical ventilation in neonatal intensive care units at the selected hospitals affiliated to Shahid Beheshti University of Medical Sciences were selected and observed by the event sampling method in 2015. Data were gathered through a demographic questionnaire for nurses and hospitalized newborns, a checklist of nursing care related to weaning from mechanical ventilation. The data were analyzed using descriptive statistics and Chi-square test at the significance level less than 0.05. Results: Conformity rate of nursing care related to weaning neonates from mechanical ventilation to standards, was 68.3 percent, and compliance with the standards of care was 71.4 percent before weaning, 65.7 percent during weaning and 66.4 percent after weaning. Conclusion: Nursing cares related to weaning neonates from mechanical ventilation are far from standards, and for its improvement, applying clinical guideline for neonatal nursing care and clinical supervision by managers for optimizing its implementation are suggested.